Impact of tropical cyclone precipitation on fluvial discharge in the LancangMekong river basin - Chen,A; Wang,J; Toumi,R; Huang,H; Yang,L; Chen,D; He,B; Liu,J (Geophysical Research Letters, 2025)
Tropical cyclone precipitation (TCP) and associated floods have caused widespread damage globally. Despite growing evidence of significant changes in the activity of tropical cyclones (TCs) in recent decades, the influence of TCs on regional flooding remains poorly understood. Here, we distinguish the role of TCs in fluvial discharge by explicitly simulating discharge with and without observed TCP in the LancangMekong River Basin, a vulnerable TC hotspot. Our results show that TCs typically contributed approximately 30% of annual maximum discharge during 1967–2015. However, for rare and high-magnitude floods (long return periods), TCs are the dominant driver of extreme discharge events. Moreover, spatial changes in TC-induced discharge are closely related to changes in TCP and TC tracks, showing increasing trends upstream but decreasing trends downstream. This study reveals significant spatiotemporal differences in TC-induced discharges and provides a methodology for quantifying the role of TCs in fluvial discharge.